Regional Autonomy Political Politics Of Regional Liability Reports To Regional Representatives In The Implementation Of Local Government - Cynthia Hadita (NOMOI Law Review, 2020)
Regional autonomy can not be separated from political power, including the dynamics of the revision of relevant legislation pertaining to local government information report liability regional head for legislature.However, it is necessary to study the politics of regional autonomy through legislation that can provide only partial or partial benefits.The issue to be discussed is concerning the politics of regional autonomy law and its implications related to the report on the responsibility of the regional head to the regional legislative assembly.The research method used is normative juridical.The results showed that (1) the administration of regional government is related to the 5th precepts of Pancasila, Article 18 of the 1945 Constitution of the Republic of Indonesia, Article 71 of the Regional Government Law, which shows the dynamics of changes that are pragmatic and has substantial changes with the revision of the Regional Government Law.(2) The political implications of the regional autonomy law related to the report of the regional head are now only recommendation and corrective, but the regional people's representative council cannot easily overthrow the regional head that has been directly elected by the people.Keywords: Politics,Regional autonomy,Implication.